Juveniles Before Courts. On Some General Principles and Practice (Archives of Criminology, 2008)
The purpose of the article is to examine the treatment of minors by Polish courts, pointing out the essence and relevance of this issue. The article covers the practice of Polish courts in dealing with minors from the 16th century until the 21st century. The author also raises the issue of differences in the treatment of minors accused of delinquency and those prosecuted for committing a punishable act. In the text Tadeusz Bojarski also carries out a comparative analysis of juvenile cases in courts and the types of acts committed by juvenile sand discusses the breakdown of measures handed down to them on the basis of data from the Statistics Division of the Ministry of Justice between 1999 and 2004. In conclusion, the author draws attention to the increase in unruly behaviour among minors since the early 1980s. According to Bojarski, the main reasons for this trend are a decrease in the effectiveness of educational measures taken in conjunction with a decline in moral social principles, an increase in adult crime, and high unemployment.